In silico Screening and Heterologous Expression of a Polyethylene Terephthalate Hydrolase (PETase)-Like Enzyme (SM14est) With Polycaprolactone (PCL)-Degrading Activity, From the Marine Sponge-Derived Strain Streptomyces sp. SM14 - Almeida, Eduardo L.; Carrillo Rincón, Andrés Felipe; Jackson, Stephen A.; Dobson, Alan D. W. (Frontiers in Microbiology, 2019)
Plastics, such as the polyethylene terephthalate (PET), are widely used for various industrial applications, due to their physicochemical properties which are particularly useful in the packaging industry. However, due to improper plastic waste management and difficulties in recycling; post-consumer plastic waste has become a pressing issue for both the environment and for human health. Hence, novel technologies and methods of processing plastic waste are required to address these issues. Enzymatic-assisted hydrolysis of synthetic polymers has been proposed as a potentially more efficient and environment-friendly alternative to the currently employed methods. Recently, a number of PET hydrolases have been described, and in particular a PETase derived from the Ideonella sakaiensis 201-F6 (IsPETase), which appears to be the most efficient and substrate-specific bacterial PET hydrolase enzyme discovered to date. In order to further investigate the class of PETase-like enzymes, we employed an in silico based screening approach on the biotechnologically relevant genus Streptomyces, including terrestrial and marine isolates; in a search for potential PETase homologs. From a total of 52 genomes analysed, we were able to identify 3 potential PETase-like enzymes, all of which were derived from marine-sponge associated Streptomyces isolates. A candidate PETase-like gene (SM14est) was identified in Streptomyces sp. SM14. Further in silico characterisation of the SM14est protein sequence and its potential three-dimensional structure were performed and compared to the well characterised IsPETase. Both the serine hydrolase motif Gly-x1-Ser-x2-Gly and the catalytic triad Ser, Asp, His are conserved in both sequences. Molecular docking experiments indicated that the SM14est enzyme possessed the capacity to bind plastics as substrates. Finally, polyesterase activity was confirmed using a polycaprolactone (PCL) plate clearing assay which is a model substrate for plastics degradation; following heterologous expression of SM14est in E. coli, with secretion being facilitated by the native Streptomyces signal peptide. These findings provide further insights into this important class of PETase-like enzymes.